Co-expression and Transcriptome Analysis of Marchantia polymorpha Transcription Factors Supports Class C ARFs as Independent Actors of an Ancient Auxin Regulatory Module - Flores-Sandoval, Eduardo; Romani, Facundo; Bowman, John L. (Frontiers in Plant Science, 2018)
We performed differential gene expression (DGE) and co-expression analyses with genes encoding components of hormonal signaling pathways and the ~400 annotated transcription factors (TFs) of M. polymorpha across multiple developmental stages of the life cycle. We identify a putative auxin-related co-expression module that has significant overlap with transcripts induced in auxin-treated tissues. Consistent with phylogenetic and functional studies, the class C ARF, MpARF3, is not part of the auxin-related co-expression module and instead is associated with transcripts enriched in gamete-producing gametangiophores. We analyse the Mparf3 and MpmiR160 mutant transcriptomes in the context of coexpression to suggest that MpARF3 antagonizes the reproductive transition via activating the MpMIR11671 and MpMIR529c precursors whose encoded microRNAs target SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) transcripts of MpSPL1 and MpSPL2. Both MpSPL genes are part of the MpARF3 co-expression group corroborating their functional significance. We provide evidence of the independence of MpARF3 from the auxin-signalling module and provide new testable hypotheses on the role of auxin-related genes in patterning meristems and differentiation events in liverworts.